Thromboembolic complications of COVID-19: the combined effect of a pro-coagulant pattern and an endothelial thrombo-inflammatory syndrome. Issue 11 (November 2020) - Vernuccio, F.; Lombardo, F.P.; Cannella, R.; Panzuto, F.; Giambelluca, D.; Arzanauskaite, M.; Midiri, M.; Cabassa, P.
Abstract : Coronavirus disease 2019 (COVID-19) is a newly emerging human infectious disease that has quickly become a worldwide threat to health, mainly causing severe acute respiratory syndrome. In addition to the widely described respiratory syndrome, COVID-19 may cause life-treating complications directly or indirectly related to this infection. Among these, thrombotic complications have emerged as an important issue in patients with COVID-19 infection, particularly in patients in intensive care units. Thrombotic complications due to COVID-19 are likely to occur due to a pro-coagulant pattern encountered in some of these patients or to a progressive endothelial thrombo-inflammatory syndrome causing microvascular disease. In the present authors' experience, from five different hospitals in Italy and the UK, imaging has proved its utility in identifying these COVID-19-related thrombotic complications, with translational clinical relevance. The aim of this review is to illustrate thromboembolic complications directly or indirectly related to COVID-19 disease. Specifically, this review will show complications related to thromboembolism due to a pro-coagulant pattern from those likely related to an endothelial thrombo-inflammatory syndrome.